Volume 13 Number 2 2017
DOI: 10.18057/ijasc.2017.13.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on the Fundamental Mechanical Features of Cable-Supported Ribbed Beam Composite Slab Structure

Abstract: ABSTRACT:In this study, experiments were carried out to investigate the fundamental mechanical features of the cable-supported ribbed beam composite slab structure (CBS). A 1:5 scaled physical model was designed, fabricated and tested. The feasibility and rationality of the CBS fabrication and construction are discussed and justified. The theoretical analysis used to predict the deflection and member forces is verified. It is shown that the CBS is equipped with high stiffness and behaves linearly in terms of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…After analyzing the results of the full-scale impact test motions recorded by the high-speed camera and load cell, it was found that the braking time of the falling object was about 0.65 s, and the time taken from touching the net to the maximum impact distance was about 0.28 s, whereas the maximum impact distance was about 2.166 m. The entire interception process of the impact test can be divided into the following three stages [19][20][21] :…”
Section: Test Resultsmentioning
confidence: 99%
“…After analyzing the results of the full-scale impact test motions recorded by the high-speed camera and load cell, it was found that the braking time of the falling object was about 0.65 s, and the time taken from touching the net to the maximum impact distance was about 0.28 s, whereas the maximum impact distance was about 2.166 m. The entire interception process of the impact test can be divided into the following three stages [19][20][21] :…”
Section: Test Resultsmentioning
confidence: 99%